The impact of users' trust on intention to use the mobile medical platform: Evidence from China - He, Jinjiang (Frontiers in Public Health, 2023)
Introduction The mobile medical platform effectively complements offline medical services as it can provide patients with broader and more convenient medical services, effectively solving the shortage of medical resources in the public health system. Although the public interest in healthcare service platforms continues to rise, the market data shows that the adoption and acceptance have not reached a high level. How to increase the utilization rate of the mobile medical platform to relieve medical pressure has become an urgent issue to be discussed. Based on the framework of “trust-intention” this research introduces innovation acceptance and technical risk concerns as the two moderating variables to attempt to build a research model of users' intention to use the mobile medical platform. The analysis illustrated that users' trust in the mobile medical platform would positively affect their use intention. The researchers further explored the moderating role of innovation acceptance and technical risk concerns. Methods Use questionnaire to collect data in China, then use the OLS least square method for the regression test. Results The results showed that users with high personal innovation acceptance would positively promote the relationship between trust and use intention. In contrast, users who are more concerned about the risks of innovative technologies will weaken the relationship between trust and use intention. Discussion The findings theoretically extend the academic research of use intention to the specific context of the mobile medical platform and enrich the research framework of “trust-intention”.